Boundedness of the Segal-Bargmann Transform on Fractional Hermite-Sobolev Spaces. (19th January 2017) - Cho, Hong Rae; Choi, Hyunil; Lee, Han-Wool
Abstract : Let s ∈ R and 2 ≤ p ≤ ∞ . We prove that the Segal-Bargmann transform B is a bounded operator from fractional Hermite-Sobolev spaces W H s, p R n to fractional Fock-Sobolev spaces F R s, p .